Vitamin D status, sleep patterns, genetic susceptibility, and the risk of incident adult-onset asthma: a large prospective cohort study - Chang, Qinyu; Zhu, Yiqun; Zhou, Guowei; Liang, Huaying; Li, Dianwu; Cheng, Jun; Pan, Pinhua; Zhang, Yan (Frontiers in Nutrition, 2023)
Introduction: Vitamin D has been known to be associated with asthma, particularly in children, while the evidence among adults is limited and inconclusive. To investigate the association between serum vitamin D concentrations and the incidence of adult-onset asthma, and the modified effect caused by sleep pattern and genetic risk. Methods: A prospective cohort study with 307,872 participants aged 37–73 years was conducted based on the UK Biobank, with a median follow-up of 12 years. Cox proportional hazard model was applied to evaluate the association between vitamin D status and incident adult-onset asthma, and the modified effect was investigated by conducting stratified analysis according to sleep pattern score and genetic risk score, and subgroup analyses were performed by sex, age, BMI, and smoking status as well. Results: Individuals with optimal vitamin D concentration was associated with around 11.1% reduced risk of incident asthma compared to those participants with deficient vitamin D (HR = 0.889; 95% CI: 0.820-0.964; p = 0.005). Moreover, stratification analysis demonstrated that the protective effect of vitamin D on asthma risk was modified by sleep patterns or genetic susceptibility, with the strongest protective effect being observed in the subpopulation with a moderate sleep pattern (HR = 0.883; 95% CI: 0.797-0.977; p = 0.016) and a moderate genetic risk (HR = 0.817; 95% CI: 0.711-0.938; p = 0.004). In subgroup analyses, the protective effect of optimal vitamin D levels was only significant among men, individuals younger than 60 years of age, overweight individuals, and current or previous smokers. Conclusion: Increased serum vitamin D levels were associated with a lower risk of incident adult-onset asthma and this association was modified by sleep patterns and genetic predisposition to some extent.